ETIKA KOMUNIKASI PEMASARAN (LIVE STREAMING SHOPPING) DI MEDIA SOSIAL DALAM PERSPEKTIF HUKUM EKONOMI SYARIAH - Jumriani, Jumriani (Al-Amwal : Journal of Islamic Economic Law, 2022)
The increase of online sales on social media allows marketers to interact online with more consumers. As part of communication and a form of product marketing, interactions that occur between marketers and potential customers must be based on applicable ethics. Ethics is important in marketing communications to create customer loyalty and online shop existence. Islam teaches ethical guidelines in communication, including marketing communications on social media. The purpose of this study is to describe the nature of marketing communication ethics and how marketing communication ethics is in an Islamic perspective. This article is a qualitative research in the nature of literature study. Data analysis techniques were carried out by data reduction, data presentation and drawing conclusions. The results of the study show that the essence of marketing communication ethics is ethics or rules regarding the right and wrong actions of communication in marketing products on social media, both verbal and non-verbal communication. In Islam, six qaulans are taught (qaulan sadida, qaulan ma’rufa, qaulan layyinan, qaulan karimah, qaulan baligha and qaulan maysura) which are basic principles in communication, including marketing communications on social media. In addition, there are five muamalah guidelines taught by the Prophet Muhammad, namely Amanah, Fathanah, Istiqamah, Tabligh (nonverbal communication) and Siddiq (verbal communication).